Combined effect of hydrogen embrittlement and corrosion on the cracking behaviour of C110 low alloy steel in O2-contaminated H2S environment. (January 2022) - Long, Yan; Song, Wenwen; Fu, Anqing; Xie, Junfeng; Feng, Yaorong; Bai, Zhenquan; Yin, Chengxian; Ma, Qingwei; Ji, Nan; Kuang, Xianren
Abstract: The cracking behavior of sulfide stress cracking resistant C110 steel in O2 -contaminated H2 S environment was investigated by cracking and corrosion simulation tests. With the increase of O2 partial pressure, the cracking susceptibility and corrosion rate of C110 steel significantly increased. The O2 ingress affects the whole cracking behaviour involving a multi-stage process: the oxidation reactions of H2 S, the corrosion reactions on the metal surface and the degradation and cracking of martensitic multiscale boundaries. The cracking mechanism of C110 steel in H2 S and O2 -containing environment is attributed to the combined effect of hydrogen embrittlement and anodic dissolution. Graphical Abstract: ga1 Highlights: Cracking susceptibility and corrosion rate of C110 steel significantly increase with the increase of O2 partial pressure. The ingress of O2 into H2 S-containing solution induces oxidation reactions of H2 S. Dissolution and oxidation of mackinawite result in the formation of porous corrosion product films. Cracking mechanism is attributed to the combined effect of hydrogen embrittlement and anodic dissolution.